Collective action for water harvesting irrigation in the Lerma-Chapala Basin, Mexico - Scott, Christopher A.; Silva-Ochoa, Paula (International Food Policy Research Institute, 2001)
Water and watersheds are difficult to separate for management purposes. Providing irrigation as a supplement to rainfall for crop production requires considerable collective action at the watershed level to mobilize labor and other resources, as well as to make decisions and implement the distribution of benefits. Small-scale water harvesting irrigation systems in Mexico have endured for centuries. They now face considerable challenges with changes in the ejido property rights over land and water, the growing importance of alternative sources of livelihoods, and increasing scarcity and competition for water within the river basins. Two case studies of water harvesting irrigation systems in the Lerma-Chapala Basin illustrate the response of communities to these challenges. In the first community, earlier collective action to build the irrigation reservoir provided a platform to address catchment resource use. Water here was less scarce than in the second community, allowing for good crop productivity through sufficient irrigation. Water scarcity in the second community increases crop risk; expected sorghum yields during the period of field study did not justify harvesting costs and the crop was used as stover. Members of the second community increased their dependence on off- farm income sources, but still responded collectively to external forces claiming the water." (text of Abstract)